Impact of noise in operating theater: A surgeon's and anesthesiologist's perspective - Pritika Srivastava; Premalatha Shetty; Sameep Shetty; Madhusudan Upadya; Aditya Nandan (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Noise is often considered as an undesirable sound. Excess noise is a health threat that deteriorates one's concentration and communication. Noise in the operating theater can be disturbing, impairs communication, and can lead to stress. The aim of this survey was to assimilate information about the perspective of surgeons and anesthesiologists regarding noise in the operating theater and whether it affects their work atmosphere. Methods: A questionnaire consisting of 15 closed-ended questions excluding one open-ended question was given to surgeons from various specialties and anesthesiologists. The subjective response were analyzed and documented. Data analysis was done using descriptive statistics. Association was found out using Chi-square test. Results: We collected a total of 290 responses, of which 87.6% (n = 254) considered noise to increase the stress level and deteriorates the quality of teamwork (83.8%, n = 243). Noise affects communication among the staff (86.2%, n = 250) and decreases their concentration level (85.5%, n = 248) which could be harmful in view of the patient's safety. 87.9% (n = 255) of the participants were in favor of limiting the number of people in the operating theater. Nonetheless, 73% (n = 211) considered music has a calming effect and were in favor of music in the operating theater. Conclusion: Noise in the operating theater can have distressing effects on surgeons, jeopardizing the patient's safety. However, a flip side to this is that music is considered to have a calming and soothing effect decreasing the anxiety and stress levels.